Religiusitas, lingkungan dan pembelian green product pada konsumen generasi Z - Firmansyah, Fani; Purnamasari, Puji Endah; Djakfar, Muhammad (Fakultas Ekonomi, UIN Maliki Malang, 2019)
The formation of consumer attitudes will shape a person's intention to do or not, and that intention will influence the formation of consumer behavior. The purpose of this study is to fill the gap with previous research by investigating the role of religiosity, an essential part of a person's belief system, in the relationship between environmental variables and the intention to purchase green products / environmentally friendly products. Questionnaire or pre-test testing was carried out by distributing questionnaires to students of State Universities in Malang in more significant numbers to obtain primary data. The method of analysis in research is the method of Moderated Regression Analysis (MRA). The results of the study indicate that religiosity is related to spiritual values that influence one's actions in making decisions. Religiosity is very important in one's life. So that generation Z who has a high level of religiosity will think of the environment for the actions they do during the purchase activity. Thus generation Z will choose environmentally friendly products (green products) so that the surrounding environment is safe and avoid environmental damage.